Adaptasi Pembelajaran Daring Penggunaan E Learning terhadap Guru SD dalam Menghadapi Tatanan Kehidupan Baru di Masa Pandemi Covid-19 di Kampung Benayah Kecamatan Pusako Kabupaten Siak - M. Yogi Isjoni; Dina Syaflita; Naila Fauza; Diah Anugrah Dipuja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Benayah Subdistrict, Siak Regency has 8 State Elementary Schools spread across various from Benayah Subdistrict. Teachers use media and learning resources that are still limited. This is due to the lack of information and lack of facilitation in developing teacher competence in using the internet based on E-Learning. Based on these conditions, the use of internet based on E-Learning is still not optimal. This service activity will be carried out in July - September 2020. This service activity is carried out in three stages, namely the preparation stage, the implementation stage and the final stage. With this service activity, it is hoped that State Elementary School teachers in Benayah District, Siak Regency can improve teacher competence in using the Internet based on E-Learning, especially Google Classroom and using it in the learning process.